2013
DOI: 10.1063/1.4825352
|View full text |Cite
|
Sign up to set email alerts
|

Off-resonance energy absorption in a linear Paul trap due to mass selective resonant quenching

Abstract: Linear Paul traps (LPT) are used in many experimental studies such as mass spectrometry, atom-ion collisions, and ion-molecule reactions. Mass selective resonant quenching (MSRQ) is implemented in LPT either to identify a charged particle's mass or to remove unwanted ions from a controlled experimental environment. In the latter case, MSRQ can introduce undesired heating to co-trapped ions of different mass, whose secular motion is off resonance with the quenching ac field, which we call off-resonance energy a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…For a detailed discussion of our group's simulations, see Refs. [20,56]. The most important factor in predicting the ion cloud's thermalized mean secular energy (from which one can assign a temperature, assuming a MB speed distribution) is the size of the MOT when the LPT is loaded via PI from a MOT [3,20].…”
Section: Fig 3 (Color Online)mentioning
confidence: 99%
See 2 more Smart Citations
“…For a detailed discussion of our group's simulations, see Refs. [20,56]. The most important factor in predicting the ion cloud's thermalized mean secular energy (from which one can assign a temperature, assuming a MB speed distribution) is the size of the MOT when the LPT is loaded via PI from a MOT [3,20].…”
Section: Fig 3 (Color Online)mentioning
confidence: 99%
“…To remove the undesired NaJ ions, we add to the driving rf voltage a small mass selective resonant quenching (MSRQ) [53,56,61,62] voltage with amplitude Vrad = 0.625 ± 0.005 V at a frequency 157 ± 1 kHz, which corresponds to the measured second harmonic secular frequency 2 [cor/{2rr)] for NaJ. The MSRQ signal resonantly drives the secular motion of the co-trapped NaJ until the molecular ion's energy exceeds the LPT's trap depth.…”
Section: Fig 3 (Color Online)mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regime, the ions are created and then immediately ejected from the trap with minimal effect on the trapped ions. The Smith group at UCONN has also implemented secular frequency excitation to remove unwanted Na + 2 ions, produced through PAI, from their experiments [53]. It may also be possible to use an intercombination MOT, in e.g.…”
Section: Mot Produced Ionsmentioning
confidence: 99%
“…In our experience, we have found that these ions can typically be ejected from the trap by changing the Mathieu a and q parameters to eject the unwanted ions. Secular excitation has been used in other experiments [53] to remove unwanted ions, but it often has the undesirable effect that the excited ions heat and eject the other ions in the trap. Finally, it is also possible to load molecular ions into the trap by first trapping an atomic ion of interest, usually produced by ionization of a neutral atomic gas, and then leaking in neutral molecular gas to react with the atomic ions and produce the desired molecular ions.…”
Section: Generation Of Molecular Ionsmentioning
confidence: 99%